Addition of Papaya Leaf Meal to Commercial Feed on the Performance of Grower Phase Laying Hens - Nurdiansyah, Fahrian Eka; Mulyono, Ali Mursyid Wahyu; Sukaryani, Sri (Jurnal Biologi Tropis, 2024)
Grower phase layers are chickens aged 5 to 12 weeks. This study aims to determine the effect of papaya leaf meal addition on the performance of laying hens in the grower phase using 72 laying hens aged 7 to 10 weeks. This study is an experimental study using a completely randomized design (CRD) with 4 treatments and 3 replications. Data were analyzed using Anova Analysis of Variance (CRD) one-way pattern with the help of SPSS Version 16. Weight Gain and Feed Conversion were unaffected by the addition of papaya leaf flour to its feed up to a concentration of 3%, according to the findings. The weight gain of laying hens during the enlargement phase was unaffected by the addition of papaya leaf flour up to 3%. The expansion of papaya leaf flour to the feed of laying hens in the producer stage on feed transformation was not altogether unique or the equivalent. The conclusion is that the feed consumption of laying hens in the grower phase can be influenced by the addition of papaya leaf flour in its feed up to a concentration of 3%, but did not affect Weight Gain or Feed Conversion.